(untitled) (Scientific journal of the Fergana State University, 2023)
The study of betulin and its derivatives is of great importance, since the programs of mathematical modeling enable a qualitative study of the relationship between structure-spectrum-properties. As a result of the theoretical search, it is possible to determine still non-synthesized highly-biologically active derivatives of betulin.